Characterization of FMR1 Repeat Expansion and Intragenic Variants by Indirect Sequence Capture - Grosso, Valentina; Marcolungo, Luca; Maestri, Simone; Alfano, Massimiliano; Lavezzari, Denise; Iadarola, Barbara; Salviati, Alessandro; Mariotti, Barbara; Botta, Annalisa; D’Apice, Maria Rosaria; Novelli, Giuseppe; Delledonne, Massimo; et al. (Frontiers in Genetics, 2021)
Traditional methods for the analysis of repeat expansions, which underlie genetic disorders such as fragile X syndrome (FXS), lack single-nucleotide resolution in repeat analysis and the ability to characterize causative variants outside the repeat array. These drawbacks can be overcome by long-read and short-read sequencing, respectively. However, the routine application of next-generation sequencing in the clinic requires target enrichment, and none of the available methods allows parallel analysis of long-DNA-fragments using both sequencing technologies. In this study, we investigated the use of indirect sequence capture (Xdrop technology) coupled to Nanopore and Illumina sequencing to characterize FMR1, the gene responsible of FXS. We achieved the efficient enrichment (> 200×) of large target DNA fragments (~60-80 kbp) encompassing the entire FMR1 gene. The analysis of Xdrop-enriched samples by Nanopore long-read sequencing allowed the complete characterization of repeat lengths in samples with normal, pre-mutation and full mutation status (> 1 kbp), and correctly identified repeat interruptions relevant for disease prognosis and transmission. Single-nucleotide variants (SNVs) and small insertions/deletions (indels) could be detected in the same samples by Illumina short-read sequencing, completing the mutational testing through the identification of pathogenic variants within the FMR1 gene, when no typical CGG repeat expansion is detected. The study successfully demonstrated the parallel analysis of repeat expansions and SNVs/indels in the FMR1 gene at single-nucleotide resolution by combining Xdrop enrichment with two next-generation sequencing approaches. With the appropriate optimization necessary for the clinical settings, the system could facilitate both the study of genotype-phenotype correlation in FXS and enable a more efficient diagnosis and genetic counselling for patients and their relatives.